2020
DOI: 10.1073/pnas.2000804117
|View full text |Cite
|
Sign up to set email alerts
|

Local exposure to school shootings and youth antidepressant use

Abstract: While over 240,000 American students experienced a school shooting in the last two decades, little is known about the impacts of these events on the mental health of surviving youth. Using large-scale prescription data from 2006 to 2015, we examine the effects of 44 school shootings on youth antidepressant use. Our empirical strategy compares the number of antidepressant prescriptions written by providers practicing 0 to 5 miles from a school that experienced a shooting (treatment areas) to the number of presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 44 publications
6
31
0
Order By: Relevance
“…Prior studies have found that children with self-reported neighborhood gun violence exposure have increased rates of mental health diagnoses, including anxiety, depression, and posttraumatic stress disorder, and mental health symptoms, including withdrawn behavior, irritability, and disruptive behaviors in school . A recent study found an increase in children’s self-reported anxiety and depression symptoms in the 12 months following gun homicides occurring within a mile of their home or school, while another study found an increase in youth antidepressant use in the 2 years after exposure to a school shooting …”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have found that children with self-reported neighborhood gun violence exposure have increased rates of mental health diagnoses, including anxiety, depression, and posttraumatic stress disorder, and mental health symptoms, including withdrawn behavior, irritability, and disruptive behaviors in school . A recent study found an increase in children’s self-reported anxiety and depression symptoms in the 12 months following gun homicides occurring within a mile of their home or school, while another study found an increase in youth antidepressant use in the 2 years after exposure to a school shooting …”
Section: Introductionmentioning
confidence: 99%
“…Closer proximity to the shooting was associated with greater post-traumatic stress symptomology, depression, anxiety, anger, and disconnection in students, faculty, and staff [17][18][19]; this phenomenon was explained by the occurrence of specific thinking styles-negative cognitions and problematic patterns of rumination-following campus shootings [18,19]. In addition, a study of 44 shootings found that students exposed to school shooting fatalities had increased and persistent antidepressant use within two years of the shooting event [20]. Some survivors experience post-traumatic growth after campus shootings.…”
Section: Affective Responses To Mass Shootingmentioning
confidence: 99%
“…In the past, events such as 9/11 ( Laugharne et al, 2007 ; Lowell et al, 2018 ; Neria et al, 2011 ; Yehuda, 2002 ), school shootings ( Rossin-Slater et al, 2020 ), or natural disasters such as earthquakes ( Garfin et al, 2014 ) or hurricanes ( Ironson et al, 1997 ) have caused surges in mental health problems. The Great Recession in 2007-2009 lead to an increase in mental health issues ( Margerison-Zilko et al, 2016 ).…”
Section: The Need For Stress Research During the Current Covid-19 Pandemicmentioning
confidence: 99%